Noninvasive Imaging Prior to Biliary Interventions - Catania, Roberta; Dasyam, Anil K.; Miller, Frank H.; Borhani, Amir A. (Seminars in Interventional Radiology, 2021)
Noninvasive imaging is a crucial and initial step in the diagnostic algorithm of patients with suspected biliary pathology and directs the subsequent diagnostic and therapeutic workup, including the endoluminal and percutaneous biliary interventions. This article reviews the current noninvasive imaging methods for the evaluation of biliary system and further discusses their roles in the diagnostic workup of different biliary disease.
Keywords: biliary; imaging; MRI; MRCP; CT